2010
DOI: 10.1242/dev.046797
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of macrophage migration and ventral nerve cord development in Drosophila embryos

Abstract: SUMMARYDuring embryonic development, Drosophila macrophages (haemocytes) undergo a series of stereotypical migrations to disperse throughout the embryo. One major migratory route is along the ventral nerve cord (VNC), where haemocytes are required for the correct development of this tissue. We show, for the first time, that a reciprocal relationship exists between haemocytes and the VNC and that defects in nerve cord development prevent haemocyte migration along this structure. Using live imaging, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 41 publications
(80 reference statements)
0
76
1
Order By: Relevance
“…Surprisingly we found that both Slit and its receptors Robo and Robo2 were actually required for migration along the VNC, 4 suggesting an attractive role with respect to hemocyte migration (compare the position of hemocytes in Fig. 2A and B).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Surprisingly we found that both Slit and its receptors Robo and Robo2 were actually required for migration along the VNC, 4 suggesting an attractive role with respect to hemocyte migration (compare the position of hemocytes in Fig. 2A and B).…”
mentioning
confidence: 83%
“…2A and B). 4 Hemocytes remained tightly constrained within areas that are accessible to the injected dye (Fig. 2C).…”
Section: Interdependence Of Hemocyte Migration and Ventral Nerve Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent findings hint that migrating cells in other systems might also exploit existing permeability to access new tissue environments. Mouse dendritic cells and Drosophila hemocytes appear to rely on tissue permeability and tissue remodeling, respectively, during migration (Baluk et al, 2007;Evans et al, 2010;Pflicke and Sixt, 2009). Additionally, the idea has been raised that because the vasculature within tumors is grossly compromised, it might not present an efficient barrier for cancer cell migration (Chung et al, 2010;Madsen and Sahai, 2010).…”
Section: Research Reportmentioning
confidence: 99%
“…11,12 They share many characteristics with the mammalian blood cells development and function and it was hypothesized that have evolved from a common ancestor. 13,14 Drosophila hemocytes originate in the procephalic mesoderm and can be categorized into three main classes.…”
Section: Hemocyte Dispersal and Chemotaxis During Development And Tismentioning
confidence: 99%